VALUE AND PRICE: ECONOMIC AND ETHICAL ASPECTS OF MODERN PHARMACEUTICAL BUSINESS (RETAIL SEGMENT) - Natalia Vladimirovna Kuzina (Science and Innovation Center Publishing House, 2016)
Transition of Medicine and Pharmacy to commercialization, optimization of medical institutions, and increasing demands for profitability in the Pharmacy business, the privatization process and power redistribution – 2015, to the full extent affecting the data sphere, leads to a revision of many traditional values and demands: criteria of economic efficiency, productivity, sales technology, corporate ethics and visitor service standards. Based on more than seven years of practice in the segment of medical and pharmaceutical services the present paper defines the given issues, suggests their solution in compliance with all ethical and psychological requirements for the (pursuit) implementation of the mentioned type of activity. Purpose (object) – identification of main issues of colliding requirements` area of economic efficiency of pharmacy segment (state pharmacy) in general and working practice of the personnel in particular with ethical criteria, relevant to the profession. We used the methods of observation and generalization, survey and interviews (patients, pharmacy staff), psychodiagnostics. Result of study: development of recommendations on recruitment, labor, sales techniques and ethics of communication with patients (pharmaceutical deontology). Results obtained are recommended for use in modern business – pharmacy segment, in state public pharmaceutical institutions, focused on sales.